PENINGKATAN KETERAMPILAN GERAK DASAR LOKOMOTOR MELALUI PERMAINAN TRADISIONAL GOBAK SODOR PADA SISWA KELAS V SDN LABAN 02 KEC. MOJOLABAN - Sunanto, Rachmad; Gatot Jariono; Vera Septi Sistiasih; Nur Subekti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research was conducted to determine the application and influence of the traditional game gobak sodor in improving basic locomotor movements in class V students at SDN Laban 02 Kec. Mojolaban and the benefits of research: 1. Improving basic locomotor movements for running, 2. Increasing the ability and professionalism of Physical Education teachers, 3. Increasing students' learning abilities. Classroom Action Research (PTK) is carried out in two cycles consisting of 4 stages, planning, action, observation and reflection. The results of the research show that the application of the traditional game gobak sodor improves basic locomotor running movements in class V students at SDN Laban 02 Kec. Mojolaban. From the results of observations of 20 students. In cycle I there were 10 students who received the "complete" criteria with 50% learning completeness. There were 4 students with the information "good" and 20% learning completeness, 6 students with "sufficient" information and 30% learning completion, and 10 students with the "inadequate" information and getting the criteria "not complete" with 50% learning completeness. Meanwhile, Cycle II experienced an increase in the form of 20 students getting the "complete" criteria with 100% learning completeness. 4 students with a description of "very good" and 20% learning completeness, 5 students with a "good" statement and 25% learning completeness, and 11 students with a "fair" statement and 55% learning completeness.